The accelerated weathering aging of a water-borne styrene acrylic coating - Vuong, Nguyen Thien; Linh, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
The aging of a water-borne styrene acrylic coating in the artificial weathering environment of a QUV/condensation weathering chamber equipped with UVB-313 fluorescent lamps has been investigated by using both chemical structure analyses (IR, UV-Vis) and measuring weigh loss and discoloration. The obtained results indicated that under the effects of UV radiation, oxygen, heat and moisture, the coating exhibited various chemical structure changes. These modifications can be linked to several mechanisms including the photolysis, photo-oxidative and hydrolysis reactions that caused a reduction of characteristic IR absorption bands for the alkane C-H, ester C-O- and C6H5 groups and the generation of photo-oxidative products (hydroperoxide, carboxylic acid and conjugated double bonds). These chemical changes result in the weight loss and yellowing of the coating. The obtained information was useful to better understand  the degradation mechanisms of the coating during accelerated weathering. Keywords. Accelerated weathering, aging, styrene acrylic emulsion, FTIR, UV-Vis, weight loss, discoloration